Delayed-onset postoperative endophthalmitis secondary to Exophiala. (17th February 2015) - Quintero-Estades, Jose Alberto; Walter, Scott; Valenzuela, Felipe; Amescua, Guillermo
Abstract : Exophiala is a genus of slow-growing, melanin-producing, saprophytic fungi most commonly found in soil, faeces and decaying plant matter. It is an unusual fungal pathogen capable of causing a variety of ophthalmic manifestations, including keratitis, scleritis and endophthalmitis. In this report, we present a rare case of delayed-onset postoperative endophthalmitis confined to the anterior segment, secondary to Exophiala species. Previous reported cases of delayed-onset postoperative endophthalmitis have been treated medically, with suboptimal outcomes. Our experience supports the use of anterior segment surgery to clear the nidus of disease combined with intravitreal voriconazole to prevent recurrence of the infection.